Implementasi Peraturan Daerah Kota Kupang Nomor 7 Tahun 2015 Tentang Bangunan Gedung Studi Di Kecamatan Kelapa Lima Kota Kupang - Djata, Stiven Djara; Yohanes, Saryono; Monteiro, Yosef Mario (Law Faculty, Nusa Cendana University, 2024)
This research aims to find out to what extent the implementation of Kupang City Regional Regulation Number 7 of 2015 concerning Buildings, in Kelapa Lima District, Kupang City and what factors are obstacles to its implementation. The research method used in this research is Empirical Juridical, namely legal facts relating to matters relating to community members in implementing statutory regulations including Kupang City Regional Regulations which are the object of study in this research or certain situations, which give rise to gaps between das solen and das sein or between practice theory, ineffective application of law, deviant behavior or behavior, situations in people's lives that are starting to experience rapid transformational changes. The approach method used is a sociological juridical approach as well as a conceptual approach and the types of data used in this research are primary data (interviews), secondary (laws) and tertiary (dictionaries). The results of the research show that the implementation of concerning Buildings in Lasiana Village and Oesapa Village as a whole reached 60%. This indicates that the implementation of these regulations is quite good, although there are still 40% who do not use building permits. And the inhibiting factor is the low level of human resources and public legal awareness.